Scintillation characteristics of heavily doped CsI:Tl, IO₃ crystals - Shpilinskaya, A.L.; Кudin, A.M.; Trefilova, L.N.; Zosim, D.J. (Вопросы атомной науки и техники, 2019)
The effect of IO⁻₃ ions on spectrometric characteristic of CsI:Tl crystal has been considered. It has been shown that co-doping of CsI:Tl crystal by IO⁻₃ anions permits to obtain clear ingots with increased thallium concentration up to CTl ~ 0.9 mole % in which the concentration quenching of photo- or radioluminescence do not observed. It has been shown that the decay of solid solution in CsI:Tl, IO₃ crystals is not observed, at least up to CTl ~ 0.5 mole %, as evidenced by a good energy resolution (R = 6.3%) of samples with the specified Tl concentration and this also evidenced by a larger segregation coefficient of thallium in CsI:Tl, IO₃ crystals (k = 0.24 contrary to k = 0.19 in CsI:Tl). An explanation of thallium solid solution stability in CsI matrix has been proposed which based on experimental fact of complex formation. Compensation of elastic stresses of opposite sign due to complex formation results in preventing of nucleation for solid solution decay.